Bio-synthesis of bacterial cellulose from ramie textile waste for high-efficiency Cu(II) adsorption - Shihang Ma; Guoguo Xi; Xiangyuan Feng; Qi Yang; Zhenghong Peng; Dong Qiu; Yuqin Hu; Xin Zhao; Lifeng Cheng; Shengwen Duan (Scientific Reports)
Abstract The current study aims at the high-value utilization of ramie textile waste and explores a bio-synthetic pathway to convert waste ramie fibers into bacterial cellulose (BC). Ramie fibers were treated with commercial cellulase (C2730) and the hydrolysate was used as a base medium (RFH) for BC synthesis by fermentation. The enzymatic hydrolysis parameters were optimized by response surface methodology, yielding an optimal temperature of 40 °C, 64 h, and an enzyme dosage of 5.7%. Under these optimized conditions, the resultant yield of reducing sugars was 31.24 ± 0.37 g/L. And then the Novacetimonas hansenii HX1 strain isolated from kombucha was used for fermentation production of BC. The study found that adding yeast extract into RFH can significantly increase BC production, and 7.2 g/L BC can be produced within 7 days. The physical and chemical properties of BC were then analyzed, including Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and Thermogravimetric analysis (TGA), confirming its type I α cellulose structure and good thermal stability. In particular, BC shows efficient adsorption capacity for Cu(II) ions in aqueous solution, with the highest adsorption efficiency reaching 95.62%. This research not only provides a new way to recycle textile waste, but also lays the foundation for the application of BC in the field of environmental remediation.